Local organizational determinants of local-international NGO collaboration. Issue 6 (3rd June 2021) - Tran, Long; AbouAssi, Khaldoun
ABSTRACT: Collaborative relations between international and local non-governmental organizations (NGOs) have often been analysed in terms of their nature and impacts. This study explores several local organizational characteristics that may explain the existence of such collaboration in the first place. Drawing upon a set of organizational theories and original data from a recent survey of 223 local NGOs in Lebanon, the study offers novel empirical evidence that international NGOs may reach and empower a subset of local NGOs better than others, which could exert distributional and undesirable effects on local NGO ecosystems.